PEMBELAJARAN MATEMATIKA DENGAN MODEL SAVI BERORIENTASI PAKEM - Christina Khaidir (Ta'dib, 2012)
Several international surveys and national examinations show that learning Mathematics in Indonesia have not expected optimum result. This is not only indicated by students’ low test score only but also by their low interest and negative image on the subject. In response to the above phenomena, paradigm in education, especially in learning Mathematics begins to shift from learning that places students as passive knowledge receivers into facilitating them to construct active knowledge. This article discusses learning model of SAVI (Somatic, Auditory, Visual and Intellectual) that promotes students’ active and independent learning based on PAKEM (active, creative, effective and fun learning). It is, therefore, expected that the offered model improve students’ interest and their image upon Mathematics subject as well.Kata kunci: pembelajaran matematika, model pembelajaran SAVI, pembelajaran berorientasi PAKEM.